Can remote green hydrogen production play a key role in decarbonizing Europe in the future? A cradle-to-gate LCA of hydrogen production in Austria, Belgium, and Iceland. (29th May 2023) - Vilbergsson, Kristjan V.; Dillman, Kevin; Emami, Nargessadat; Ásbjörnsson, Einar J.; Heinonen, Jukka; Finger, David C.
Abstract: Hydrogen can play a key role in decarbonizing industrial and transportation processes. As the European demand for hydrogen rises, several EU member states have been looking into ways to import remotely-produced hydrogen (H2 ) to fulfill their local needs. This cradle-to-gate LCA study assesses the H2 production in Iceland using local renewable energy sources, including the transport to potential gates in Austria and Belgium and compares it with locally produced H2 at the European sites. Our results indicate that the Global Warming Potential (GWP) of H2 production depends primarily on the energy mix, while transportation of H2 generates a minor impact. Furthermore, in its current state, H2 production in Iceland through Polymer electrolyte membrane electrolysis (PEM-EC) yields over 13- and 21 times lower GHG emissions compared respectively to Austria and Belgium. Based on these results, we conclude that remotely produced hydrogen can play an important part in decarbonizing European carbon-intensive industries. Highlights: It is important to include both spatial and temporal perspectives into an assessment of remote hydrogen production. Icelandic green hydrogen production and shipping to Europe has a high potential. Transport does not affect the footprint significantly, compared to H2 production in worse grid conditions. Liquefaction is the largest contributor to the transportation phase. Intermittent operation reduces the full load hours significantly and, increases the carbon footprint of green H2 .